The Role of Rhizopus oligosporus in Enhancing Protein and Mineral Bioavailability in Tempeh: A Literature Review - Riza Nazila Azri; Alimatusakdia Panggabean; Citra Partika Dwi; Audia Fadilla; Zia Syamsia Balqis; Enni Halimatussa’diyah Pakpahan (Asosiasi Dosen Muda Indonesia, 2026)
Tempeh is a fermented soybean-based food that plays an important role in meeting the protein and mineral needs of the Indonesian population. The fermentation process of tempeh involves the mold Rhizopus oligosporus, which contributes to the transformation of soybean chemical components through enzymatic activity. This article aims to review the role of Rhizopus oligosporus in enhancing protein and mineral bioavailability in tempeh based on a literature review of Indonesian scientific journals and academic books published over the last five years. The method employed was a literature review focusing on accredited national publications related to tempeh fermentation, protein digestibility, and mineral bioavailability. The findings indicate that Rhizopus oligosporus produces proteolytic enzymes capable of hydrolyzing complex soybean proteins into peptides and free amino acids, thereby improving protein digestibility and biological quality. In addition, phytase enzyme activity during fermentation plays a significant role in reducing phytic acid content, an antinutritional compound, which subsequently enhances the availability of essential minerals such as iron and calcium. The increased bioavailability of protein and minerals positions tempeh as a potential functional food that can contribute to improving community nutritional status. Therefore, optimizing tempeh fermentation using Rhizopus oligosporus should continue to be developed to enhance nutritional quality and strengthen the competitiveness of tempeh as a superior local food product.